KEBIJAKAN HEDGING DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Studi Empiris Pada Perusahaan Non Finansial yang Terdaftar Di BEI Periode 2012-2014) - Goklas, Fernando; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2016)
Foreign exchange risk is one of the biggest risks facing the company in its activities in international trade. Changes in foreign currency exchange rates may result in losses to the company. Therefore, companies must anticipate doing risk management one of which is through hedging policy. This study aimed to analyze the effect of liquidity, managerial ownership, dividend policy, leverage, cash flow volatility, growth opportunity and control variables company size on the derivative instruments hedging policy on non-financial companies listed on the Stock Exchange 2012-2014.This study using purposive sampling method in order to obtain a total of 27 sample companies. This study used logistic regression analysis to determine the variables that affect the use of derivative instruments as hedging policy tool. Tests using logistic regression analysis only Overall Model Fit Test, Cox and Snell's R Square and Nagelkerke's R Square, Hosmer and Lemeshow Goodness of Fit Test, Classification Table and logistic regression analysis, so it does not require normality test.The results showed empirical evidence there are two variables that significantly influence the policy of hedging derivative instruments. Variable liquidity and volatility of cash flow positive and significant effect and in accordance with the predicted against the policy of hedging with derivatives insturmen. As for the other independent variables that significantly affect dividend policy does not however have the effect as predicted direction. In variable managerial ownership, leverage and growth opportunity not show direction as predicted. Control variables firm size did not show significant results on the dependent variable.